Systematic review and meta-analysis of the efficacy and safety of oseltamivir (Tamiflu) in the treatment of Coronavirus Disease 2019 (COVID-19) - Aliyu, Basiru; Raji, Yakubu Egigogo; Chee, Hui Yee; Wong, Mui Yun; Sekawi, Zamberi (Public Library of Science, 2022)
Efforts are ongoing by researchers globally to develop new drugs or repurpose existing ones for treating COVID-19. Thus, this led to the use of oseltamivir, an antiviral drug used for treating influenza A and B viruses, as a trial drug for COVID-19. However, available evidence from clinical studies has shown conflicting results on the effectiveness of oseltamivir in COVID-19 treatment. Therefore, this systematic review and meta-analysis was performed to assess the clinical safety and efficacy of oseltamivir for treating COVID-19. The study was conducted according to the PRISMA guidelines, and the priori protocol was registered in PROSPERO (CRD42021270821). Five databases were searched, the identified records were screened, and followed by the extraction of relevant data. Eight observational studies from four Asian countries were included. A random-effects model was used to pool odds ratios (ORs), mean differences (MD), and their 95% confidence intervals (CI) for the study analysis. Survival was not significantly different between all categories of oseltamivir and the comparison groups analysed. The duration of hospitalisation was significantly shorter in the oseltamivir group following sensitivity analysis (MD -5.95, 95% CI -9.91--1.99 p = 0.003, heterogeneity I2 0%, p = 0.37). The virological, laboratory and radiological response rates were all not in favour of oseltamivir. However, the electrocardiographic safety parameters were found to be better in the oseltamivir group. However, more studies are needed to establish robust evidence on the effectiveness or otherwise of oseltamivir usage for treating COVID-19.